Algunas consideraciones sobre la estructura temporal de tasas de interés del gobierno en México - Santiago García-Verdú (Banco de México, 2011)
– This paper, first, reviews briefly the literature on the term structure of interest rates, citing some of the most important studies done on the topic for the Mexican case in the last years. In addition, the development of the government debt market is described. Second, evidence against the expectation hypothesis is shown and the deviations of the term structure from this hypothesis are examined. Third, it is documented that much of the variability of the term structure is due to changes in its level. Fourth, some of the statistics of the term structure are associated with macroeconomic variables, specifically the shortterm rate and the output gap as measured with the IGAE index. Regarding this last point, evidence is found that changes in the term structure of interest rates' slope are associated with the monetary policy stand along the business cycle. The nominal interest rates used in the analysis go from July 2002 to June 2011.
Keywords: E43; G12; 330; Term Structure of Interest Rates; Expectation Hypothesis; Principal Component Analysis; Nominal Interest Rates; Zinsstruktur; Zins; Erwartungstheorie; Hauptkomponentenanalyse; Mexiko